50 Shades of Blackness - Holloway, Linda J. M. (Journal of poetry therapy, 2025)
Colorism is an age-old problem. This is where a person is given preferential treatment based on the color of their skin. Oftentimes in the Black community, dark-skinned people are treated less favorably compared to lighter-skinned people. As a result, many dark-complexioned Black people despise the color of their skin because they are deemed as socially unacceptable. Since Black people come in different shades the author created this poem to give relevance to all shades of Blackness. This poem is designed to show appreciation and celebration for all variations of skin tones in the Black community.